2016
DOI: 10.1128/genomea.00592-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Nonagglutinating Lactococcus garvieae Strain 122061 Isolated from Yellowtail in Japan

Abstract: Nonagglutinating Lactococcus garvieae has been isolated from diseased farmed yellowtail in Japan since 2012. In this study, the complete genome and plasmid sequence of nonagglutinating L. garvieae strain 122061 was determined, to our knowledge, for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The first strain was the most closely related to strain JJJN1 derived from the so‐iuy mullet ( Planiliza haematocheilus ) in South Korea in 2017, whereas the third strain was almost identical to strain MS210922A derived from the greater amberjack in Japan in 2021 (Akmal et al, 2022). On the contrary, L21‐20 was the most closely related to strain 122,061, isolated from the yellowtail amberjack in Japan in 2012 (Nishiki et al, 2016). The strain 122,061 was reported as a divergent serotype of L. garviae , but the phylogenetic analysis indicates that it belongs to L. formosensis .…”
Section: Resultsmentioning
confidence: 99%
“…The first strain was the most closely related to strain JJJN1 derived from the so‐iuy mullet ( Planiliza haematocheilus ) in South Korea in 2017, whereas the third strain was almost identical to strain MS210922A derived from the greater amberjack in Japan in 2021 (Akmal et al, 2022). On the contrary, L21‐20 was the most closely related to strain 122,061, isolated from the yellowtail amberjack in Japan in 2012 (Nishiki et al, 2016). The strain 122,061 was reported as a divergent serotype of L. garviae , but the phylogenetic analysis indicates that it belongs to L. formosensis .…”
Section: Resultsmentioning
confidence: 99%
“…The agglutinated and non‐agglutinated strains were designated as serotype I and serotype II, respectively (Fukuda et al, 2015; Ohbayashi et al, 2017). Furthermore, average nucleotide identity (ANI) revealed that serotype I (AP090129) and serotype II (122061) were 90.7% similar to each other (Nishiki et al, 2016). Recently, a new strain, which is non‐reactive to both serotype I and II antisera has been isolated (Akmal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the maintenance of large, non-transmissible plasmids, such as pLG50, despite their high cost to the bacteria, depends on the positive selection of genes with a high adaptive value: virulence genes, bacteriocins, immunity proteins, etc. [54,72].…”
Section: Recombination Between L Garvieae and Other Species Of The Cl...mentioning
confidence: 99%